Improving student learning achievements through application of the student teams achievement divisions (STAD) method - Sri Budiyono; Ngumarno Ngumarno (English, 2019)
The learning process in the world of education (ranging from elementary, secondary, and tertiary education) needs innovation and serious renewal creation because in reality so far there are still many learning models that are still conventional, there is no visible improvisation in learning, far from modern learning model in accordance with the demands of the times and the surrounding environmental conditions in which students or students are located. The research aims: 1) to describe how the conditions of second-semester student learning before using the Student Team Achievement Divisions (STAD) method; 2) to describe whether the STAD method of learning the at Widya Dharma Klaten University of II semester student achievement in the 2017/2018 Academic year can increase or not. The work steps taken consisted of five main components, namely presentation in class; form a team; make a quiz; score individually; and awards. Data analysis techniques by using descriptive analysis that is by finding the level of activity, Mean (M), learning outcomes, and learning completeness. The results showed that applying the STAD method there was a significant increase in learning outcomes.